Indicator Analysis of the Economic Development of Polish Regions in the Context of the Implementation of the Concept of Sustainable Development - Barska, Anetta; Jędrzejczak-Gas, Janina (European Journal of Sustainable Development, 2019)
The aim of the article is to present the regional differentiation of indicators characterizing the economic development of Polish regions in the context of the progress made in the implementation of the concept of sustainable development in 2010 and 2017. The authors focused primarily on determining the position of Lubuskie Province on the economic map of Poland. The article proposes a set of indicators monitoring one of the areas of sustainable development - economic development, which also take into account other areas of sustainable development, i.e. social development, environmental development, and institutional-political development. The main criterion for the selection of indicators were substantive premises and their completeness and accessibility across the regions. The analysis and evaluation of the proposed indicators (explanatory variables) were conducted within five thematic areas which mark the economic development of the regions and which are important from the standpoint of the sustainable development concept: 1) Potential of the economy 2) Innovativeness of the economy 3) Economic activity of enterprises, 4) Production and transportation, 5) Economic activity of households. The article consists of two sections. In the first section, based on literature review, the most important issues regarding the concept of sustainable development and the state of scientific research on the indicators of sustainable development at regional level are presented. The second section addresses the concept of indicator analysis on the basis of which an assessment of economic development of 16 Polish regions was carried out and the position of Lubuskie Province was determined against the backdrop of the other regions. The findings prompted an answer to the question concerning the economic development of Polish regions, and in particular of Lubuskie Province, in the context of the concept of sustainable development. Keywords: indicator analysis, region, sustainable development, economic development, Poland